Comparison of landing kinematics and kinetics between experienced and novice volleyball players during block and spike jumps - Sébastien Garcia; N. Delattre; E. Berton; G. Divrechy; G. Rao (BMC, 2022)
Abstract Background The practice of volleyball requires many jumps. During landing, anterior cruciate ligament injuries may occur with high-risk lower limb kinematics and kinetics. Differences in landing strategies between experienced and novice volleyball players have not been fully explored. The purpose of the study was to compare lower limb kinematics and kinetics in experienced and novice volleyball players when performing volleyball specific jumps. Methods A total of 30 healthy males, 15 experienced and 15 novice volleyball players, participated in the study. Participants performed block and spike jumps at a controlled jump height. Hip, knee and ankle joints angles at initial ground contact and ranges of motion in the sagittal plane, knee joint angles and moments in the frontal plane, vertical ground reaction force peak and loading rate were analyzed to investigate the expertise effect. Results Experienced volleyball players landed with larger ankle dorsiflexion range of motion compared to novices. For the spike jump, experienced players landed with larger ankle plantarflexion angles at initial contact and larger ankle dorsiflexion ranges of motion, and for the block jump, they landed with larger knee flexion ranges of motion. Experienced players jumped significantly higher than novices. No difference was found in vertical ground reaction force peaks and loading rates. Conclusions Although the experienced group jumped higher than the novice group, no difference was found in ground reaction force parameters. These findings highlight that the experience of volleyball players acquired during regular trainings and competitions may play an important role in landing kinematics and kinetics to reduce the injury risk.